The impact of ESG scores on corporate financial performance: A study of non-financial firms listed in the UK - Al-Tarawneh, Ahmad; Tayeh, Mohammad; Iskandrani, Majd; Obeidat, Muhanned (Asian Economic and Financial Review, 2024)
This study investigates the relationship between Environmental, Social, and Governance (ESG) scores and firm financial performance, measured by Tobin's Q and Return on Assets (ROA), for non-financial firms listed in the UK. The study sample included 188 firms from 2015 to 2023. Panel regression was used to account for the firm- and time-specific unobservable variables, while the Generalized Method of Moments (GMM) estimation was used to account for endogeneity concerns. The results reveal a significant negative relationship between ESG combined score and Tobin’s Q, suggesting that higher ESG ratings are associated with lower firm valuation. Additionally, the impact of the Governance score on Tobin’s Q is negative and statistically significant at the 1% level. The results validate the trade-off theory, indicating that investors may view investments in ESG initiatives less favorably at least in the short run, suggesting that listed companies with strong stakeholder-oriented practices are not rewarded with a premium price. The findings underscore the importance of ESG initiatives for management and decision makers to enhance investor awareness about the role of ESG initiatives in contributing to long-term shareholder value through sustainable growth, improved stakeholder relationships, and effective risk management.